THE COVERAGE OF MENTAL HEALTH ISSUES IN THE WORKS OF IMAM ABU HAMID GHAZALI - Eshonkulova Guljahon Abdukakhorovna (Bright Mind Publishing, 2025)
The article presents ideas about the legacy of Imam Ghazali, its study today, its coverage in pedagogical and psychological sources, and its understudied area.
Keywords: Spirit, soul, mind, heritage, friend, science, friendship, happiness, spirituality, spirituality, enlightenment, profession, harmony.